Formação para a cidadania na educação básica brasileira - Hellinger, João Ricardo Jurgensen (2018)
This research deals with training for citizenship in Brazilian basic education. Having as main objective, to unveil the ideal of citizen contained in the legislations related to this level of education. As a condition for the development of the work, we sought to investigate the concepts of "citizenship" and "formation for citizenship", first in ancient Greece, through the ideal of paidéia, and then in the modern European world, with conceptions of bildung and halbbildung. In Brazil, research was concentrated at the end of the nineteenth century until the present, especially from 1994 to 2016, in which the civil, political, social and republican rights of the Brazilian citizen were portrayed, as well as their inevitable correlation with public education . Allowing the understanding of the concepts of "citizen" and "training for citizenship" in the main current educational legislation, such as the Federal Constitution of 1988; the Law of Guidelines and Bases of National Education 9394 of 1996; and the National Curricular Guidelines, both those built by the Fernando Henrique Cardoso government and the subsequent ones enacted in the Lula da Silva e Dilma Rousseff government. For this, the research was based on authors such as Adorno, Aristotle José Murilo de Carvalho, Engels, Marx, Jaeger, Locke, Marshall, Décio Saes, Demerval Saviani, Frigotto, Manacorda, Milton Santos, among others, who contributed to the foundation and depth of work. The chosen methodology prioritized the construction of an explanatory research of qualitative and documentary nature. The legislation approached, as well as the authors' contributions to the subject of the research, showed that training for citizenship is a common theme that is aimed at as the main educational legislation, however, there are few specificities in the law that guide the conception of citizens and the way in which they should be trained. By relating it, moreover, to the modern concepts of formation, it is understood that, historically, Brazilian public education resembles, in principle, much more, with the adaptive design of halbbildung, semiformation, than with the project of bildung, formation cultural. These characteristics were maintained both in the government of Fernando Henrique Cardoso and in the PT government of Lula da Silva and Dilma Rousseff, although with evident differences for public education.